2016
DOI: 10.1186/s12884-016-0937-5
|View full text |Cite
|
Sign up to set email alerts
|

Hormone concentrations throughout uncomplicated pregnancies: a longitudinal study

Abstract: BackgroundEvidence suggests that the hormonal milieu of pregnancy is an important determinant of subsequent cancer and other chronic diseases in both the mother and the offspring. Many of the existing maternity and birth cohorts include specimens drawn only once during pregnancy. How well a single blood specimen collected during a pregnancy characterizes exposure to these hormones throughout gestation, and also in subsequent pregnancies, is not well understood.MethodsWe used serial serum samples from 71 pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 41 publications
(56 reference statements)
9
122
2
1
Order By: Relevance
“…Androgen concentrations are relatively stable in pregnancy (24), however, we excluded FMC members in sensitivity analyses given that all women were pregnant at the time they provided a blood sample. Finally, we conducted a sensitivity analysis after exclusion of women diagnosed within two years after blood donation.…”
Section: Methodsmentioning
confidence: 99%
“…Androgen concentrations are relatively stable in pregnancy (24), however, we excluded FMC members in sensitivity analyses given that all women were pregnant at the time they provided a blood sample. Finally, we conducted a sensitivity analysis after exclusion of women diagnosed within two years after blood donation.…”
Section: Methodsmentioning
confidence: 99%
“…Parity represents a complex addition to the estimation given the role of immune factors in pregnancy such as the proliferation of regulatory T cells (39), which is suggested to protect against AD (40). In addition, estrogen levels rise up to 300-fold throughout pregnancy (41) and fall 100-1000 fold postnatally (42), often in relation to breastfeeding (8), of which the duration influences the number of total menstrual cycles within a woman's reproductive years (11,43). Parous women may also have shorter menstrual cycles and lower levels of estradiol than nulliparous women (44,45), indicating that age at first birth also influences lifetime estrogen exposure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest studies on progesterone in pregnancy showed an increasing trend of plasma progesterone from conception to delivery [12]. A more recent study by Schock et al further highlighted this increasing trend throughout pregnancy [13]. However, little is known about the distribution of serum progesterone in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%